Reactive oxygen species in polycystic ovary syndrome: Mechanistic insights into pathogenesis and therapeutic opportunities - Huanju Liu; Lihao Jin; Xiaoya Wang; Junling Shi; Yujie He; Ningxia Sun; Fu Yang (Redox Biology)
Polycystic ovary syndrome (PCOS), a common yet intricate endocrine disorder, presents persistent clinical challenges due to its complex pathogenesis. Reactive oxygen species (ROS), highly reactive molecules, have emerged as critical contributors to PCOS development and represent potential therapeutic targets. This review comprehensively explores the diverse roles of ROS in PCOS pathogenesis, particularly their contributions to metabolic dysfunction and hormonal imbalance. It further assesses the therapeutic potential of ROS-targeted interventions, summarizing antioxidant therapy advancements, underlying mechanisms, and current challenges. By consolidating recent research, this review highlights the profound significance of ROS in PCOS, aiming to inspire innovative pathogenesis research, improve clinical management, and establish a robust theoretical foundation for more effective PCOS treatment strategies.